## Solving Logarithmic Equations

We want to find the solutions to

log(8x) - log(1 + ) = 2.

Let us note that the equation is only defined when the input for the logarithms is positive. Thus we need x > 0 and 1 + > 0. Since the second condition is automatically satisfied when x > 0, the equation is defined for all positive x.

We begin by combining the two logarithmic expressions into one expression, using the rule that

log = log a - log b.

Consequently our equation becomes

log = 2.

This is equivalent to saying that

= 102 = 100

Next we multiply both sides by the denominator on the left:

8x = 100(1 + ),

or equivalently

8x - 100 = 100.

Next we square both sides to eliminate the square root term:

(8x - 100)2 = 10, 000x  64x2 - 1, 600x + 10, 000 = 10, 000x.

Simplifying we obtain the quadratic equation

8x2 - 1, 450x + 1, 250 = 0.

Using the quadratic formula, we compute two solutions to this quadratic equation as

x = .

Numerically the solutions equal x1 180.383 and x2 0.86621.

It is essential that you now check both answers in the original equation!

For x1,

log(8x1) - log(1 + ) 2.000,

thus x1 is a solution to the equation.

On the other hand,

log(8x2) - log(1 + ) .555,

thus x2 is not a solution to the equation.

Answer: The equation has exactly one solution, namely

x = 180.383.

[Back to Rules of Logarithms] [Back to Exponential Functions]

[Algebra]
[Algebra] [Trigonometry] [Complex Variables]